The Impacts of Explicit and Implicit Instructions of English Connectors on EFL Students’ Reading Comprehension - Adjie Putra Pangestu; Jumatul Hidayah; Eka Apriani (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2021)
There have been many studies on English grammar, but a dearth of studies has been conducted in the cross-sectional fields such as seeking how the field of grammar makes contributions to reading comprehension. Accordingly, the current study sought to find out the impacts of explicit and implicit instructions of English connectors on EFL students’ reading comprehension. 50 third semester students from an English department at a university in Bengkulu were incorporated as the samples. Adopting a quasi-experimental method, those 50 students were split into two classes, the so-called experimental and control classes. Students in the experimental class were taught English connectors explicitly, and those of the control class were taught English connectors implicitly. Before eight times of treatments in the form of the two ways of instructions, students of the two group were given a valid and reliable reading comprehension pre-test, and a similar construct of post-test was given after the eighth treatments ended. The data of the current study were analyzed by deploying paired sample t-test and independent sample t-test. The present study revealed that explicit and implicit instructions of English connectors had positive impacts on EFL students’ reading comprehension. However, the explicit instruction of English connectors enhanced EFL students’ reading comprehension more significantly and more effectively. It is recommended that further studies be conducted to replicate the present study in different contexts for the sake of providing rich data to confirm the current study’s results.